2000
DOI: 10.1038/77288
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of human T cells from a tissue-engineered thymic organoid

Abstract: Biocompatible inorganic matrices have been used to enhance bone repair by integrating with endogenous bone architecture. Hypothesizing that a three-dimensional framework might support reconstruction of other tissues as well, we assessed the capacity of a tantalum-coated carbon matrix to support reconstitution of functioning thymic tissue. We engineered a thymic organoid by seeding matrices with murine thymic stroma. Co-culture of human bone marrow-derived hematopoietic progenitor cells within this xenogeneic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 23 publications
1
92
0
Order By: Relevance
“…Current culture systems that support the development of human T cells from bone marrow precursor cells use animal or unrelated human tissues, making them less desirable for the production of T cells for use in humans (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Current culture systems that support the development of human T cells from bone marrow precursor cells use animal or unrelated human tissues, making them less desirable for the production of T cells for use in humans (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…This system has been reported to yield functional, singlepositive T cells from huCD34 1 HSCs after 14 days [13,14]. After 3 wk of co-culture, there was a significantly increased number of mononuclear cells in thymic but not in skin co-cultures ( Fig.…”
Section: Hla-b7mentioning
confidence: 89%
“…CellFoam cell-culture dishes 10 mm in diameter  1 mm in depth with an average pore density of 80 pores per inch (Cytomatrix) were pre-cultured with fragmented thymic or skin tissue as described previously [13]. After 22-35 days purified huCD34…”
Section: -D Cell-culture Matrixmentioning
confidence: 99%
“…The experimental study of human T-cell lymphopoiesis has been largely limited to the use of the OP9 expressing the Notch ligand Delta-like 1 (OP9--DL1) SCID-hu mouse model (Galy et al 1993), murine and human thymic organ cultures (Rosenzweig et al 1994;Yeoman et al 1993), and human thymic monolayers (Poznansky et al 2000). Zuniga-Pflucker demonstrated that retrovirally transduced DL1 Notch ligand to the OP9 bone marrow stromal cell line inhibited the development of B cells but favored the development of T cells from fetal liver-derived HSCs and CB-derived HSCs (La Motte-Mohs et al 2005).…”
Section: Introductionmentioning
confidence: 99%